Implication of Macroalgal Bloom to Soil Organic Carbon Stock in Seagrass Meadows - A Case Study in South Hainan, China - Chen, Shunyang; Chen, Shiquan; Chen, Bin; Wu, Zhongjie; An, Wenshuo; Luo, Lizhen; Wang, Jing; Xie, Limei; Zhang, Jing; Chen, Guangcheng (Frontiers in Marine Science, 2022)
The adverse impact of macroalgal blooms associated with nutrient enrichment on seagrass habitats and carbon storage potential is an ecological concern. In the present study, the soil carbon stock and sources were compared between a seagrass meadow where a serious macroalgal bloom occurred (site M) and an adjacent site without apparent macroalgae (site R) in a nutrient-enriched lagoon in South Hainan Island, China, to test whether macroalgal blooms associated with nutrient enrichment would impact the soil carbon in seagrass meadows. The soil organic carbon (OC) and total nitrogen contents in the top 30 cm at site M were significantly lower than those at site R. The soil OC stocks (top 30 cm) were 3.4 and 5.4 Mg C ha-1 at site M and site R, respectively, and no difference was observed between sampling stations with different distances offshore at either site. Soil δ13C was more enriched and closer to the δ13C of seagrass tissues at site R than at site M. Bayesian stable isotope mixing model analyses suggested that seagrass-derived material contributed ~50% to soil OC at site R, while at site M, the contribution was reduced to ~25%. The results suggested that macroalgal blooms associated with nutrient enrichment could drive the loss of seagrass-derived OC and the OC stock in the soil, which is worthy of full attention for blue carbon conservation.